The impact of human resource practices on job performance and turnover intentions in Palestinian nonprofit organizations / Anas M S Abukhalifa - Anas M S , Abukhalifa (2024)
Leaning on the social exchange theory and job demand resource theory, this study strived to examine the cross-level longitudinal effect of ability, motivation, and opportunity strategic HRM bundles on job performance and turnover intention via the mediating mechanism of work engagement and the moderating role of psychological capital. Longitudinal data were gathered from 270 paid employees employed by 30 non-profit organizations in Palestine and were analyzed using Hierarchical Linear Modelling. The findings disclosed that all strategic HRM bundles had a significant positive cross-level longitudinal effect on work engagement and job performance as well as a significant longitudinal negative effect on turnover intention. In addition, the results revealed that work engagement mediated partially the longitudinal effect of strategic HRM bundles on job performance and turnover intention. More importantly, the study uncovered that the opportunity-enhancing bundle was the strongest predictor of work engagement and job performance whereas the motivation-enhancing bundle was the best predictor of turnover intention. The findings disclosed that psychological capital strengthened the positive longitudinal relationship between work engagement and job performance but however did not moderate the relationship between work engagement and turnover intention. This study plugs multiple theoretical, methodological, and empirical gaps within the literature on strategic HRM, the non-profit sector and positive psychology. One of the most significant gaps which were filled is the novelty of the study as this study is the first to investigate the longitudinal effect of strategic HRM bundles on job performance and turnover intention in the non-profit sector worldwide. A further discussion of theoretical contributions, practical implications, and future directions is provided in detail.